2019
DOI: 10.1097/pr9.0000000000000704
|View full text |Cite
|
Sign up to set email alerts
|

Exploring assessment of medical students' competencies in pain medicine—A review

Abstract: Supplemental Digital Content is Available in the Text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 105 publications
(363 reference statements)
0
17
0
Order By: Relevance
“…Lack of training in pain management remains the most significant and fundamental obstacle to effective pain management as an inadequate emphasis on pain education for medical undergraduates may eventually reflect in poor patient care practices following graduation [7][8][9]. Medical students often begin their education in Colleges of Medicine with little or no knowledge of pain and that situation, coupled with very few hours of pain training, results in their lack of confidence in assessing adult and paediatric patients with pain [10]. It is thought that existing prevalent negative attitudes of physicians toward patients with, for example, chronic non-cancer pain begins early in medical school [11].…”
Section: Introductionmentioning
confidence: 99%
“…Lack of training in pain management remains the most significant and fundamental obstacle to effective pain management as an inadequate emphasis on pain education for medical undergraduates may eventually reflect in poor patient care practices following graduation [7][8][9]. Medical students often begin their education in Colleges of Medicine with little or no knowledge of pain and that situation, coupled with very few hours of pain training, results in their lack of confidence in assessing adult and paediatric patients with pain [10]. It is thought that existing prevalent negative attitudes of physicians toward patients with, for example, chronic non-cancer pain begins early in medical school [11].…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, approximately half of the sample equated obesity with a lower likelihood of ordering imaging, while the other half did the opposite. There are known challenges with pediatric pain assessment and management in general (Committee on Psychosocial Aspects of Child and Family Health & Task Force on Pain in Infants, Children, and Adolescents, 2001), and studies show that students pursuing healthcare degrees lack satisfactory knowledge in this area (Shipton et al, 2019; Ung et al, 2016). Such factors may contribute to the variability in responding for this item.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, a patient satisfaction survey showed that less than one-third experienced over 30% pain relief [ 2 ]. The diagnostic and management of chronic pain/NeuP should be part of any effective continuing training for general medical practitioners and neurologists [ 72 , 76 , 77 , 78 , 79 ].…”
Section: Discussionmentioning
confidence: 99%